2010
DOI: 10.1088/1742-6596/209/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the length scales between lithographic patterning and self assembly mechanisms in fabrication of semiconductor nanostructure arrays

Abstract: Abstract. We employ focused ion beam patterning of single crystal Si(100) surfaces to template the assembly of Ge(Si) nanostructure arrays. The evolution and final structures of the templated arrays are determined by combinations of transmission electron, low energy electron microscope, focused ion beam and scanning probe microscopies. It is shown how the positions of individual nanostructures may be controlled to the order of 10 nm. However, to achieve controlled spacings between elements that are in the 10 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The generation of Si-or Ge-QDs with controllable size tunability and arrangement has been the subject of considerable research starting in the 1990s [7,8]. Several approaches have been proposed for the formation of Si-and Ge-QDs, including chemical synthesis, [9] epitaxial growth, [10] deposition followed by post-annealing, [11] lithographic patterning [12], and electrostatic-gate definition based on two-dimensional electron-gas (2DEG) heterostructures [13]. The key to implementing QD devices for practical applications lies in having an unprecedentedly high degree of control over the crystallinity, size, shape, density or number, and spatial location of QDs, all of which are essentially important for optimizing device performance.…”
Section: Fabrication-related Challenges For Si/ge-qdsmentioning
confidence: 99%
“…The generation of Si-or Ge-QDs with controllable size tunability and arrangement has been the subject of considerable research starting in the 1990s [7,8]. Several approaches have been proposed for the formation of Si-and Ge-QDs, including chemical synthesis, [9] epitaxial growth, [10] deposition followed by post-annealing, [11] lithographic patterning [12], and electrostatic-gate definition based on two-dimensional electron-gas (2DEG) heterostructures [13]. The key to implementing QD devices for practical applications lies in having an unprecedentedly high degree of control over the crystallinity, size, shape, density or number, and spatial location of QDs, all of which are essentially important for optimizing device performance.…”
Section: Fabrication-related Challenges For Si/ge-qdsmentioning
confidence: 99%
“…The templating process itself (i.e., the nucleation or trapping mechanism) can take various forms. For example, ultralow dose implantation of 25 kV Ga + ions into Si(100) followed by annealing and molecular beam epitaxy (MBE) of germanium was used to fabricate Ge quantum dots (QDs) by Hull et al [42], and the location of QDs was found to be in strong correlation with the IBL pattern if the annealing conditions were selected carefully in relation to the evolving surface morphology. Other types of QDs, such as InAs and InP on GaAs substrate, and Cu 2 O on SrTiO 3 were also produced by other groups.…”
Section: Nucleation Sites For Directed Self-assembly (Dsa)mentioning
confidence: 99%
“…One strategy for controlling nanostructure location is to create topological features on the substrate surface at which nanostructures will preferentially nucleate during subsequent growth 3 – 5 . Direct milling with focused ion beams (FIB) is a promising method for such surface templating 6 . The conditions for templating can range from high implanted doses, which mill deep features 7 9 into the substrate, to low implanted doses, which either generate subtle changes in the surface topography on the order of a few nanometers or create point defects near the surface 10 14 .…”
Section: Introductionmentioning
confidence: 99%